Blended learning design : from theory to practice - Last, Barend, ....-; Jongen, Stefan, ....- (Amsterdam : Boom, 2023)
Teaching can be done in many ways: in a group or individually, face-to face or online, synchronously or asynchronously. Each of these ways requires its own approach. When you know how to combine them in the right way, you enrich the student’s learning experience. That combination is called blended learning. Activating strategies and maximizing interaction with the help of technology are essential. But what is the best blend and how do you design it?
Keywords: Onderwijs